Dietary magnesium and calcium intake is associated with lower risk of hearing loss in older adults: A cross-sectional study of NHANES - Wei, Xinmin (Frontiers in Nutrition, 2023)
Aim: Dietary intake as a modifiable factor has been reported to be associated with hearing loss (HL). The relationship between magnesium (Mg) and calcium (Ca) as common dietary nutrients and HL in the elderly has rarely been reported. This study aimed to assess the association between Mg and Ca intake and HL in older adults. Method: This cross-sectional study included participants aged 70 years from the National Health and Nutrition Examination Survey (NHANES) 2005-2006, 2009-2010, and 2017-2018. Outcomes were low-frequency [pure-tone averages (PTAs) at 500, 1000, and 2000 Hz >25 dB] and speech-frequency (PTAs at 500, 1000, 2000, and 4000 Hz >25 dB) HL. Multivariate logistic analysis was utilized to explore the association between dietary Mg and Ca intake and their combined intake (Ca/Mg, Ca*Mg) and HL, and was described as odds ratio (OR) and 95% confidence interval (CI). Results: A total of 1,858 participants were included, of which 1,052 (55.95%) had low-frequency HL and 1,349 (72.62%) had speech-frequency HL. Dietary Ca intakes [OR=0.86, 95%CI: (0.74-0.99)] and Mg intakes [OR=0.81, 95%CI: (0.68-0.95)] and Ca * Mg [OR=0.12, 95%CI: (0.02-0.87)] were associated with lower odds of low-frequency HL after adjusting for confounders. Similar, dietary Ca intakes [OR=0.85, 95%CI: (0.77-0.95)] and Mg intakes [OR=0.78, 95%CI: (0.68-0.90)] and Ca * Mg [OR=0.23, 95%CI: (0.05-0.78)] were related to lower odds of speech-frequency HL. For different levels of Mg and Ca intake, the combined intake of Ca (≥1044mg) and Mg (≥330mg) was related to lower odds of low-frequency HL [OR=0.02, 95%CI: (0.00-0.27)] and speech-frequency HL [OR=0.44, 95%CI: (0.21-0.89)]. Conclusion: Dietary intakes of Mg and Ca were associated with lower odds of HL and are a promising intervention to be further explored in older adults with HL.